Szadek w korespondencjach "Kaliszanina" - Andrysiak, Ewa (Biuletyn Szadkowski, 2009)
The journal “Kaliszanin” issued in Kalisz in 1870–1892 published central and local government decrees, information about the city and its neighborhood, historical articles, theatre reviews, political, economic and cultural news, literature, reports on the activity of social organizations, letters from readers, and correspondence from the country and from abroad. This article reviews the correspondence sent from Szadek to the journal, which provides an interesting source of information about the town and the surrounding area in the second half of 19th century.